2020
DOI: 10.1111/crj.13234
|View full text |Cite
|
Sign up to set email alerts
|

Development of spirometric reference equations for children living at high altitude

Abstract: Objectives This study was aimed to provide locally derived spirometric equations from a population of healthy children residing in Bogota, Colombia, a high‐altitude city. Methods Healthy children aged more than 6 years up to less than 18 years underwent spirometry from January 2017 to January 2018, following the recommendations made by the American Thoracic Society/European Respiratory Society (ATS/ERS) Task Force. We performed stepwise multiple regression analyses to predict each spirometric parameter. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…This group found that the predicted values at the pulmonary function level in the Latin American population are like the ones reported for American population that have come originally from Mexico [ 42 ]. A study has recently been published in which predictive equations have been performed for each spirometric variable among children living at moderate and high altitude in Colombia, which could be useful for further analysis among children [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This group found that the predicted values at the pulmonary function level in the Latin American population are like the ones reported for American population that have come originally from Mexico [ 42 ]. A study has recently been published in which predictive equations have been performed for each spirometric variable among children living at moderate and high altitude in Colombia, which could be useful for further analysis among children [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This group found that the predicted values at the pulmonary function level in the Latin American population are like the American population of Mexican origin within the NHANES III study [38]. A study has recently been published in which predictive equations have been performed for each spirometric variable among children living at moderate and high altitude in Colombia, which could be useful for further analysis among children [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recientemente, nuevos valores espirométricos se han establecido en Bogotá (2.640 metros sobre el nivel del mar (msmn)) en niños 6-17 años, donde la talla fue la mejor variable predictiva (aunque se incluyó también la edad y el peso), y cuyos resultados demostraron que los valores de VEF1 y CFV son significativamente mayores que en las ecuaciones generadas por la Global Lung Function Initiative (GLI). Esto es se debe principalmente al crecimiento acelerado del volumen torácico en relación con la estatura, que es el resultado de la adaptación a un ambiente hipóxico y disminución de la densidad del aire que ocurre en las alturas (9). También se han establecido valores de oscilometría de impulso (IOS) en niños 3-5 años que viven en Bogotá, donde nuevamente la talla fue la mejor variable predictiva y cuyos resultados muestran como límite superior normal una caída de 28% en la resistencia total de la vía aérea (R5Hz) o un incremento de 36% en la reactancia (X5Hz) post broncodilatador (10).…”
Section: Sección Serie / Seriesunclassified